Respuesta :

Step-by-step explanation:

[tex]x^{2} - 12x + 59 = 0[/tex]

Given equaiton is in the form of ax^2 +bx+c=0

we apply quadratic formula to solve for x

[tex]x= \frac{-b+-\sqrt{b^2-4ac} }{2a}[/tex]

a= 1  b = -12  and c= 59

[tex]x= \frac{12+-\sqrt{(-12)^2-4(1)(59)}}{2(1)}[/tex]

[tex]x= \frac{12+-\sqrt{92}}{2}[/tex]

[tex]x= \frac{12+-2\sqrt{23}}{2}[/tex]

Divide the 12 and square root terms by 2

[tex]x=6+-\sqrt{23}[/tex]

so [tex]x=6+\sqrt{23}[/tex]    and    [tex]x=6-\sqrt{23}[/tex]




Answer:

Solution for x:

[tex]6+\sqrt{23}i[/tex]   and   [tex]6-\sqrt{23}i[/tex]

Step-by-step explanation:

Given: [tex]x^2-12x+59=0[/tex]

It is quadratic equation and to solve for x.

using quadratic formula:

[tex]x=\dfrac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex]

where, a=1, b=-12 and c=59

Put the values into the formula

[tex]x=\dfrac{12\pm\sqrt{12^2-4\cdot 1\cdot -59}}{2(1)}[/tex]

[tex]x=\dfrac{12\pm \sqrt{-92}}{2}[/tex]

As we know, [tex]\sqrt{-1}=i[/tex]

[tex]x=6\pm\sqrt{23}i[/tex]

Exact value of x : [tex]6+\sqrt{23}i[/tex]   and   [tex]6-\sqrt{23}i[/tex]